Research Mentoring Needs of International Doctoral Counseling Students: An Interpretive Phenomenological Inquiry - S Anandavalli; John J. S. Harrichand; Rafe McCullough (Teaching and Supervision in Counseling, 2025)
The authors of this article sought to explore the research mentoring needs of International Doctoral Counseling Students (IDCS). The purpose of this inquiry was to help research mentors better support this community. Centering Relational Cultural Theory as the theoretical framework, the authors interviewed 14 participants. These individuals were identified using convenience and snowball sampling. Using interpretive phenomenological analysis, three grand themes emerged from participants’ interviews: socialization and belonging in academia, feeling invisible, and mutuality and research. Implications for research mentors and/or counselor educators, and future research are also discussed.
Keywords: international doctoral counseling students; relational cultural theory; interpretive phenomenological analysis; research mentorship; counselor education